Severe Maternal Morbidity and Hospital Cost among Hospitalized Deliveries in the United States - Chen, Han-Yang; Chauhan, Suneet P.; Blackwell, Sean C. (American Journal of Perinatology, 2018)
Objective The objective of this study was to estimate the contemporary national rate of severe maternal morbidity (SMM) and its associated hospital cost during delivery hospitalization.Study Design We conducted a retrospective study identifying all delivery hospitalizations in the United States between 2011 and 2012. We used data from the National (Nationwide) Inpatient sample of the Healthcare Cost and Utilization Project. The delivery hospitalizations with SMM were identified by having at least one of the 25 previously established list of diagnosis and procedure codes. Aggregate and mean hospital costs were estimated. A generalized linear regression model was used to examine the association between SMM and hospital costs.Results Of 7,438,946 delivery hospitalizations identified, the rate of SMM was 154 per 10,000 delivery hospitalizations. Without any SMM, the mean hospital cost was $4,300 and with any SMM, the mean hospital cost was $11,000. After adjustment, comparing to those without any SMM, the mean cost of delivery hospitalizations with any SMM was 2.1 (95% confidence interval: 2.1–2.2) times higher, and this ratio increases from 1.7-fold in those with only one SMM to 10.3-fold in those with five or more concurrent SMM.Conclusion The hospital cost with any SMM was 2.1 times higher than those without any SMM. Our findings highlight the need to identify interventions and guide research efforts to mitigate the rate of SMM and its economic burden.
Keywords: administrative data; childbirth; hospital cost; severe maternal morbidity